BIODIVERSITY MODULE BASED ON PROBLEM-BASED LEARNING LOCAL WISDOM ASSISTED BY AUGMENTED REALITY: IMPROVING STUDENTS' CRITICAL THINKING - Iwan Iwan; Jeni Jeni; Nurfathurrahmah Nurfathurrahmah (Jurnal Eduscience)
Purpose – The purpose of this study was to develop a student teaching module for biodiversity material oriented to Problem Based Learning integrated with local wisdom and assisted by augmented reality media to improve students' critical thinking skills.